Individual Freedom in the Initial Response to Covid-19 - Macip, Salvador; Yuguero, Oriol (Frontiers in Public Health, 2022)
The covid-19 pandemic has been a phenomenal challenge to global health care and will continue to be so in the upcoming months. Beyond its medical toll, covid-19 has also exacerbated pre-existing social issues and created new inequalities. This has generated a series of ethical problems that will need to be carefully analysed to avoid repeating similar mistakes in the context of other crises. Among those, we discuss here the bioethical implications of preserving individual freedom in the context of the early response to a pandemic and propose a global approach to the issue that could be applied in future health challenges.